2016
DOI: 10.1155/2016/9235080
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells: Key Players in the Shadow in Oral Inflammation and in Squamous Cell Carcinoma of the Oral Cavity

Abstract: Although mast cells (MCs) have been discovered over 130 years ago, their function was almost exclusively linked to allergic affections. At the time being, it is well known that MCs possess a great variety of roles, in both physiologic and pathologic conditions. In the oral tissues, MCs release different proinflammatory cytokines, tumor necrosis factor alpha (TNF-α), that promote leukocyte infiltration in various inflammatory states of the oral cavity. These cells play a key role in the inflammatory process and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…MCs accumulate around the tumor margins and release pro-angiogenic and angiogenic factors which favor tumor progression [17] . MCs in tissues can be identified using histochemical stains like toluidine blue, alcian blue and immunohistochemistry using tryptase, heparin, chymase and, carboxypeptidase [8] . In the present study, 1% toluidine blue stain was used for the identification and enumeration of MCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MCs accumulate around the tumor margins and release pro-angiogenic and angiogenic factors which favor tumor progression [17] . MCs in tissues can be identified using histochemical stains like toluidine blue, alcian blue and immunohistochemistry using tryptase, heparin, chymase and, carboxypeptidase [8] . In the present study, 1% toluidine blue stain was used for the identification and enumeration of MCs.…”
Section: Discussionmentioning
confidence: 99%
“…MCs can secrete angiogenic factors that enhance the angiogenesis of a tumor [8] . A previous study has shown that increased MCD and MVD in OSCC when compared to the normal oral mucosa, however, they could not demonstrate a statistically significant correlation between MCD and MVD in OSCC [18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mast cells proliferation by inflammatory cytokines induces an increase of mast cell density in inflammatory tissues (Mierke et al, ). An increase in the number of mast cells is observed in reactive inflammatory conditions (Gaje et al, ). The increased number of mast cells is also observed in allergic inflammation with local recruitment and activation of T helper 2 (Th2) lymphocytes (Hart, ).…”
Section: Introductionmentioning
confidence: 99%